Planning a barrier free environment and better quality of life based on the predictors of out-of-home of rural older Malaysian - Syed Abdul Rashid, Sharifah Norazizan (IRSSH Research Group, 2013)
Engaging in more out-of-home activities are important elements in the quality of life of the older persons. The older persons have a wide range of social and physical constraints to participate in out-of-home activities and these have implications that require accurate interpretations of an ageing society which impacts on the whole built environment. Based on the study entitled 'Activities, Access and Ageing of Older Malaysians' conducted by the author, factors that hinder or support the participation of older persons in out-of-home activities were identified. The purpose of the paper is to identify the patterns and predictors of out-of-home activities of rural older Malaysians and to understand their needs and expectations in barrier-free environment. The study found that there are significant relationships between age, perceived barriers to town and the number of out-of-home activities participated. Results highlight important factors relevant for the urban planners and policy makers in creating high quality barrier free environment that would enhance the older persons' quality of life.